Investigation on the adsorption of antibiotics from water by metal loaded sewage sludge biochar - Xiulei Fan (IWA Publishing, 2021)
Application of sewage sludge biochar as an adsorbent for antibiotics treatment has obtained special attention owning to its low cost and surface functionality. Three metal ions were selected to modify sewage sludge biochar through the pyrolysis with the metal loaded method. Fe loaded sewage sludge biochar (BC-Fe), Al loaded sewage sludge biochar (BC-Al) and Mn loaded sewage sludge biochar (BC-Mn) were characterized and used to explore the performance of adsorbing tetracycline (TC), sulfamethoxazole (SMZ) and amoxicillin (AMC). BC-Fe, BC-Al and BC-Mn possessed rougher surfaces, larger specific surface area and better pore structure. Intra-particle diffusion and Langmuir models were more suitable to describe the adsorption process. The maximum adsorption amount of TC, SMZ and AMC could reach 123.35, 99.01 and 109.89 mg/g by BC-Fe. Furthermore, the main mechanism of antibiotics adsorption by metal loaded sewage sludge biochars might be pores filling, Van der Waals forces and H-bonding. The study can not only solve the problems associated with the pollution of antibiotics from wastewater, but also reduced the treatment pressure of sewage sludge effectively.